Outer membrane vesicles in service as protein shuttles, biotic defenders, and immunological doppelgängers. (2nd September 2016) - Laughlin, Richard C.; Alaniz, Robert C.
Abstract: Characterization of host microbial interactions typically occurs on the cellular or protein level. Recently, a more thorough and accurate appreciation of cellular interactions has come into better focus with improved understanding of membrane vesicles (OMV). While OMVs are documented primarily in Gram-negative bacteria, certain Gram-positive species generate these structures, despite the obvious physical limitations of the cell envelope. Here, we briefly review the current understanding of OMVs in content and function, their role in pathogenesis, and the consequences of somatic cell gene expression on these events.